Analysis and Modeling of Faces and Gestures
DOI: 10.1007/978-3-540-75690-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Human Perambulation as a Self Calibrating Biometric

Abstract: Abstract. This paper introduces a novel method of single camera gait reconstruction which is independent of the walking direction and of the camera parameters. Recognizing people by gait has unique advantages with respect to other biometric techniques: the identification of the walking subject is completely unobtrusive and the identification can be achieved at distance. Recently much research has been conducted into the recognition of frontoparallel gait. The proposed method relies on the very nature of walkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Therefore, an automatic gait recognition system which does not depend on camera calibration and is able to recognise individuals walking towards the camera is attractive. 2D view-independent gait identification is a relatively new research area and the approaches found in literature tend to synthesise the sagittal view of the human body from other arbitrary views [12], [18], [35] or to extract gait parameters which are independent from the human pose [4], [38]. The first choice is justified by the fact that the lateral view has demonstrated the recognition capability in many works [27], [43].…”
mentioning
confidence: 99%
“…Therefore, an automatic gait recognition system which does not depend on camera calibration and is able to recognise individuals walking towards the camera is attractive. 2D view-independent gait identification is a relatively new research area and the approaches found in literature tend to synthesise the sagittal view of the human body from other arbitrary views [12], [18], [35] or to extract gait parameters which are independent from the human pose [4], [38]. The first choice is justified by the fact that the lateral view has demonstrated the recognition capability in many works [27], [43].…”
mentioning
confidence: 99%
“…The method proposed by the authors in [16] is based on four main assumptions: the nature of human gait is cyclic; subjects walk along a straight line; the distances between the bone joints are constant; and the articulated leg motion is approximately planar. Therefore, multiple periods of linear gait motion appear analogous to a single period viewed from many cameras related by linear translation and the positions of the legs joints lie in an auto-epipolar configuration.…”
Section: View-point Independent Rectificationmentioning
confidence: 99%
“…Therefore, starting from a video sequence from a single camera and without any calibration, the proposed markerless system, in junction with [16], estimates the gait parameters projected on the lateral plane.…”
Section: View-point Independent Rectificationmentioning
confidence: 99%
See 2 more Smart Citations